Combination of a Novel Genetic Variant in CFB Gene and a Pathogenic Variant in COL4A5 Gene in a Sibling Renal Disease: A Case Report - Wang, Feng-mei; Yang, Yan; Zhang, Xiao-liang; Wang, Yan-li; Tu, Yan; Liu, Bi-Cheng; Wang, Bin (Frontiers in Genetics, 2021)
Complement factor B (CFB) variants have been described to play a causative role in auto-immune associated C3 glomerulopathy (C3G) and/or atypical hemolytic uremic syndrome (aHUS) by affecting the dysregulations of alternative pathway activation. However, CFB variant concomitant with COL4A5 variant is scarce. Here, we depict two intriguing cases with concurrent novel heterozygosity for CFB c.2054_2057del (p.Ser687Profs∗16) variant and a previous reported COL4A5 c.2999G > T (p.Gly1000Val) variant in a pair of siblings. The clinical feature of either paternal CFB variant or maternal COL4A5 variant is just mild microscopic hematuria. Interestingly, their two children with paternal CFB c.2054_2057del (p.Ser687Profs∗16) variant and maternal COL4A5 c.2999G > T (p.Gly1000Val) variant presented with massive proteinuria, hematuria, and progressive renal failure with poor treatment response. Moreover, complement pathway activation in renal tissue further supports and strengthens the pathogenic role of CFB variant in the development of renal injury in the presence of COL4A5 variant. In conclusion, the rare sibling cases highlight that the extension of genetic analyses in the proband is helpful for the diagnosis and understanding of some family cluster renal diseases.